ANALISIS PROSES PEMBELAJARAN MATEMATIKA PADA ANAK BERKEBUTUHAN KHUSUS (ABK) SLOW LEARNERS DI KELAS INKLUSI (Penelitian Dilakukan di SD Al Firdaus Surakarta) - Fida Rahmantika Hadi; Tri Atmojo Kusmayadi; Budi Usodo (Jurnal Pembelajaran Matematika, 2015)
Abstract: This research aims to find out: (1) the mathematics learning process in inclusive class includes readiness of teacher before learning process, implementation and evaluation and follow up; (2) the inhibiting factors encountered of slow learners child during mathematics learning process in inclusive class and the solution to them. It was a qualitative research. The subjects were taken by purposive sampling.The subjects of this research were mathematics teacherand special assistant teacher.Data collection techniques in this research were interviews and observation. Techniques to validate that the data triangulation time. The data analysis technique used was consisted of data reduction, data display, and conclusion. The results of this study were: (1) preparation of Lesson Plan has done after one basic competence finished and any Lesson Plan modified for slow learners child. Before learning proses began, specific media teachers has been prepared for slow learners child. In evaluation and follow-up stage, teachers planned follow-up activities in remedial learning, enrichment programs, counseling services for reguler students or special needs children with the help of a special assistant teacher. (2) Factors or the difficulties which have been slow learners child was difficult about mathematics concepts, beside of that also may lost interest in the task and refused to resume the task when they was bored. The teacher resolve problems by providing mathematical concepts step by step and intens, provide additional learning time, provide motivation and provide reward.Keywords: mathematics learning process, slow learners child, inclusive